2021
DOI: 10.2147/sar.s307387
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying Addiction

Abstract: Addiction disorders/substance use disorders (SUD) are on the rise. However, many mental health care providers have never experienced SUD themselves, leading to higher chances of poor patient care through stigma, judgement, and the misunderstanding of patients. An alternative approach to understanding patients with addictive behaviors using a comparison of sex is discussed in this paper. Since most health care providers will have experienced sex, this analog can help mental health workers with no lived experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, a study done among university students in UK found conflicting results attaching alcohol use among university students to pleasure rather than a way of dealing with stress or anxiety [ 57 ]. Symptoms of anxiety can also be triggered by the stress associated with substance consumption [ 58 ]. Owing to the cross-sectional nature of this study, the causal-effect relationship between anxiety symptoms and AUD could not be determined despite some literature emphasizing that anxiety symptoms may predate AUD for this theory to hold.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study done among university students in UK found conflicting results attaching alcohol use among university students to pleasure rather than a way of dealing with stress or anxiety [ 57 ]. Symptoms of anxiety can also be triggered by the stress associated with substance consumption [ 58 ]. Owing to the cross-sectional nature of this study, the causal-effect relationship between anxiety symptoms and AUD could not be determined despite some literature emphasizing that anxiety symptoms may predate AUD for this theory to hold.…”
Section: Discussionmentioning
confidence: 99%